Aggregated neutrophil extracellular traps occlude Meibomian glands during ocular surface inflammation - Mahajan, Aparna; Hasíková, Lenka; Hampel, Ulrike; Grüneboom, Anika; Shan, Xiaomei; Herrmann, Irmgard; Garreis, Fabian; Bock, Felix; Knopf, Jasmin; Singh, Jeeshan; Mahajan, Siddharth; Leppkes, Moritz; et al. (Ocular Surface, 2021)
Purpose: Obstructive Meibomian gland dysfunction (MGD) is one of the leading causes of evaporative dry eye disease. Meibomian glands at the eyelid secrete lipids that prevent evaporation of the aqueous tear film. The pathogenesis of obstructive MGD is incompletely understood to date. Herein, we aim to investigate the pathogenesis of obstructive MGD using murine and human samples with various forms of ocular surface inflammation. Method: The presence of Neutrophil extracellular Traps (NETs) was detected with immunofluorescence analysis of ocular surface discharge and biopsy samples from patients with blepharitis. Tear fluid from patients with MGD and blepharitis were evaluated for the presence of inflammatory mediators using bead based immunoassay. Murine model of allergic eye disease (AED) was performed to investigate the role of NETs in MG occlusion. Results: we show that the ocular discharge from patients with blepharitis contains aggregated neutrophil extracellular traps (aggNETs). Furthermore, the ducts of human Meibomian glands affected by blepharitis were largely congested by aggNETs. Tear fluid from patients with MGD showed elevated neutrophil chemoattractants (C5a, IL6, IL8 and IL18). C5a and IL8 correlated with the degree of deficiency of tear fluid. In the murine model of allergic eye disease (AED), aggNETs accumulated in the MG leading to occlusion of their ducts and the retrograde pent-up of the fluid followed by acinar atrophy. Constraining aggNET formation by genetic or pharmacological inhibition of peptidyl arginine deiminase type 4 (PADI4) effectively reduced MG damage. Conclusion: We conclude that aggNETs occlude MG causing MGD after ocular surface inflammation.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Blepharitis; Meibomian gland dysfunction (MGD); Neutrophil extracellular traps (NETs); Occlusion

Corneal endothelium can be protected against cell by anti-Bax siRNA - Fuchsluger, Thomas; Thieme, Daniel; Kruse, Friedrich; Mahajan, Siddharth; Schubert, Dirk W. (The Association for Research in Vision and Ophthalmology (ARVO), 2018)
Keywords: corneal; ani-Bak

Corneal endothelium can be protected against cell death by anti-Bax and anti-Bak siRNA - Fuchsluger, Thomas; Thieme, Daniel; Kruse, Friedrich; Mahajan, Siddharth (2018)
EVALuna2:34735

Silencing of pro-apoptotic proteins as anti-apoptotic therapy for corneal endothelium - Fuchsluger, Thomas Armin; Thieme, Daniel; Kruse, Friedrich; Mahajan, Siddharth (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Suppressing Pro-Apoptotic Proteins by siRNA in Corneal Endothelial Cells Protects against Cell Death - Staehlke, Susanne; Mahajan, Siddharth; Thieme, Daniel; Trosan, Peter; Fuchsluger, Thomas A. (Biomedicines, 2024)
Corneal endothelial cells (CE) are critical for the cornea’s transparency. For severe corneal damage, corneal tissue transplantation is the most promising option for restoring vision. However, CE apoptotic cell death occurs during the storage of donor corneas for transplantation. This study used small interfering (si)RNA-mediated silencing of pro-apoptotic proteins as a novel strategy to protect CE against apoptosis. Therefore, the pro-apoptotic proteins Bax and Bak were silenced in the human corneal endothelial cell line (HCEC-12) by transfection with Accell™siRNA without any adverse effects on cell viability. When apoptosis was induced, e.g., etoposide, the caspase-3 activity and Annexin V-FITC/PI assay indicated a significantly reduced apoptosis rate in Bax+Bak-siRNA transfected HCECs compared to control (w/o siRNA). TUNEL assay in HCECs exposed also significantly lower cell death in Bax+Bak-siRNA (7.5%) compared to control (w/o siRNA: 32.8%). In ex vivo donor corneas, a significant reduction of TUNEL-positive CEs in Bax+Bak-siRNA corneas (8.1%) was detectable compared to control-treated corneas (w/o siRNA: 27.9%). In this study, we demonstrated that suppressing pro-apoptotic siRNA leads to inhibiting CE apoptosis. Gene therapy with siRNA may open a new translational approach for corneal tissue treatment in the eye bank before transplantation, leading to graft protection and prolonged graft survival.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Annexin V; anti-apoptotic Bax and Bak; apoptosis; caspase-3; confocal laser scanning microscopy; corneal endothelial cells; donor cornea; siRNA; TUNEL